1-Methylcyclopropene (1-MCP) effects on natural disease resistance in stored sweetpotato - Amoah, Robert S.; Terry, Leon A. (Wiley, 2018)
BACKGROUND The potential of 1-methylcyclopropene (1-MCP) to maintain postharvest storage of sweetpotato was studied. In two separate experiments, the orange-fleshed sweetpotato cv. Covington was fumigated with 1-MCP (1.0 μL L-1, 24 h) and roots stored at 15 oC. During storage, samples were evaluated for the respiration rate, sprout growth, weight loss, incidence of decay and changes in dry matter. The roots were further assayed for the temporal changes in individual non-structural carbohydrates and phenolic compounds in the skin and flesh tissues of the proximal (stem end), middle, and distal (root end) regions. RESULTS 1-MCP treatment reduced root weight loss and decay but respiration rate and non-structural carbohydrates were not affected. No sprouting was recorded irrespective of the treatment. 1-MCP transiently suppressed the accumulation of individual phenolic compounds, especially in the middle and distal segments. This accentuated the proximal dominance of phenolic compounds. Isochlorogenic acid A and chlorogenic acid were the dominant phenolics in the skin and flesh tissues, respectively. CONCLUSION 1-MCP treatment may have anti-decay effect and reduce weight loss. Therefore, storage trials which involve the use of continuous ethylene supplementation to inhibit sprout growth may be combined with 1-MCP to alleviate ethylene-induced weight loss and decay in sweetpotato.
Keywords: Respiration; Decay; Weight loss; Sugars; Phenolics